Teacher noticing as a driver of interaction patterns in science classrooms - Hlologelo Climant Khoza (Journal of Pedagogical Research, 2023)
Teachers' responses to student contributions in science classroom influence the resulting classroom interaction. To establish a heightened interaction, teachers need to use specific discursive moves. Using the notion of noticing as a lens, in this qualitative case study, I report on how the notion of noticing and responding with a suitable discursive move is important for science teachers to drive interaction. I use data from two South African science teachers' lessons and video-stimulated recall interviews (VSRI) to show instances where they employed specific discursive moves as a result of noticing and the interaction unfolded in a dialogic manner and instances where they 'failed' to notice a pertinent feature of a student's contribution and the interaction did not move beyond the initiation-response-evaluation (IRE) triad. I discuss the significance of teacher noticing in science classrooms as it influences how the interaction unfolds. I also offer implications for pre-service science teacher education.